Analysis of factors influencing successful Agrobacterium-mediated genetic transformation in two Bangladeshi peanut (Arachis hypogaea L.) varieties BINA Chinabadam-2 and BINA Chinabadam-6 using embryonic leaflet explant - Chowdhury, Iftekhar Mahmud (BRAC University, 2014)
A thesis submitted to BRAC University in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology